COGNITIVE STRATEGY OF JUNIOR HIGH SCHOOL STUDENTS IN LEARNING DIRECT LINE EQUATION - Arlina Arlina (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2013)
This study aims to find out: (1) the profile of cognitive strategies of junior high school students in learning equation of straight line, both in understanding the material and in problem solving, (2) description of learning result of equation of straight line of junior high school student from the type of cognitive strategy used. This research procedure through two stages, namely through the preparation stage and implementation phase. The preparation stage includes the preparation of learning tools in the form of Learning Implementation Plan (RPP), Student Book, Teacher Book, Student Activity Sheet (LKS), Cognitive Strategy Brochure, and research instrument. The things prepared in this preparation phase are validated, except the cognitive strategy brochure. While the implementation stage includes the application of learning tools to students of class VIII1 SMP Negeri 2 Bantimurung as a selected class. In the implementation phase, it is obtained: (1) cognitive strategy in understanding the material displayed in the student's book and cognitive strategy in problem solving which is shown in the LKS (qualitative data), and (2) the score of learning result test (quantitative data). The results of the analysis on the qualitative part found in general cognitive strategy profile to understand the material of straight-line equation is to underline the important things of formulas and the profile of cognitive strategy to solve the problem of straight-line equation is deductive thinking strategy. Description of learning result of equation of straight line after learning by using cognitive strategy is average score 71,68 with standard deviation 12,33 from ideal score 100. Minimum score obtained by student is 50,00 and maximum score obtained by student is 94,83 With a score range of 44.83. Students who have a cognitive strategy profile are able to highlight important things, able to make summaries and able to complete concept maps, and have experience in solving problems by applying heuristic strategies, deductive thinking, and forward thinking have learning outcomes in very high categories, whereas Students who are incapable of completing concept maps and having no advanced thinking strategy generally have high learning outcomes, and students who do not have a strategy in understanding the material and have only experience in solving problems by implementing deductive strategies have learning outcomes in the medium category And low.